Keanekaragaman Tumbuhan Tingkat Tinggi Di Desa Tlontoraja Kabupaten Pamekasan Sebagai Bahan Ajar Berbasis Kearifan Lokal - Shirta Juliyana; Yuni Gayatri (Universitas Muhammadiyah Surabaya, 2017)
Abstract: This study is aimed to determine: (1) the diversity of high-level-plant in Tlontoraja Village, Pamekasan Madura; (2) the form of teaching materials that can be made from the results of studies of high-level-plant diversity in the Village of Tlontoraja, Pamekasan Madura. This research is a descriptive research with survey method. The subjects in this study are the forest of Sumber Mata Air-Dungendak, Tlontoraja, Pamekasan, Madura. While the object of this research is all plants which are in the transects and plots. This research used transect method and sample plot which was divided into 5 blocks and each transect contains 5 plots in 20 x 20 meters. This observation was conducted to identify trees, poles, stakes and seedlings. The results showed that the highest INP with the following details; Seedling is a Pennisetum purpureum species with INP 34.66%; Stake that is a Tectona grandis species with INP 114,36%; Pole that is a species of Schoutenia ovata with INP 78,29% and tree that is species of Lannea coromandelica with INP 163,79%. The conclusions of this study are (1) the index of diversity in the forest belongs to the same category: medium, with the following details: 1.24 trees; Stakes 1.9; Pole 1.8 and seedlings 2.39; (2) The teaching material made from this research result is an encyclopedia of high-level-plants categories.